Characteristics of Patients with Type 2 Diabetes Mellitus - Aprilio, Rachmad; Sabri, Rika; Mahathir, Mahathir (Indonesian Journal of Global Health Research, 2024)
Diabetes mellitus patients are included in a vulnerable group with a higher risk of developing other diseases, thus requiring dynamic and continuous treatment Treatment options for diabetes mellitus include insulin therapy, diabetes medications, trying alternative treatments, undergoing surgery, and improving lifestyle (healthy eating habits and exercise) by consuming nutritious or healthy foods and engaging in physical activity. Self-management of diabetes refers to individual actions taken to control the condition, including treatment and prevention of complications. Some aspects of diabetes self-management include dietary regulation, physical activity/exercise, blood sugar monitoring, medication adherence, as well as self-care/foot care. Objective to determine the Characteristics of Diabetes Mellitus Patients in the Simpang Periuk Community Health Center area. The type of this research is quantitative with a descriptive design approach. The research design utilized in this study is a cross-sectional research design, which is a method involving measurements or observations at the same time and the sample size in this study consists of 36 respondents with Type 2 Diabetes Mellitus. Data was collected through interviews using a questionnaire to gather research variable data, including gender, age, education level, employment status, duration of diabetes, BMI/body mass index, and self-management. The data was then analyzed using univariate analysis. The processed data was subsequently presented in tabular form, accompanied by explanations. The research results show that more than half of the respondents are male (72.2%), and female (27.8%). The most common age group among respondents (41.7%) is 46-55 years old. Education levels also vary, with the majority (52.6%) having completed high school. In terms of occupation, (36.1%) are self-employed. The duration of having type 2 diabetes mellitus for most respondents (77.8%) is less than three years. The majority (69.4%) have a normal body mass index. More than (72.2%) of the respondents have poor self-management.